Contribution of biological maturation and power of upper and lower limbs to crawl swim performance in adolescent athletes - Paulo Francisco De Almeida-Neto; Gilmara Gomes de Assis; Brunna Rafaella Do Carmo Silva; Radamés Maciel Vítor Medeiros; Alexandre Bulhões-Correia; Vitória Monteiro Monte Oliveira; Victor Sabino de Queiros; Pablo Henrique Moura De Paiva; Paulo Moreira Silva Dantas; Breno Guilherme De Araújo Tinoco Cabral (Termedia Publishing House, 2022)
Purpose There is no consensus in literature data about the influence of biological maturation (BM) on swim performance in young athletes. We analysed the relationship of BM, upper-limb power (ULP), and lower-limb power (LLP) with adolescent athletes' performance in crawl swim. Methods This observational study determined the BM of 16 competitive swimmers (50% males and 50% females; 12.90 ± 0.88 years) by a mathematical model based on bone age and anthropometric measures. ULP and LLP were established by the horizontal launch test and the vertical and countermovement jump tests on a force platform, respectively. Swim performance was evaluated by the average speed in a 100-m crawl sprint. Results BM was related to ULP (males: r = 0.76, p = 0.001; females: r = 0.39, p = 0.02), LLP (males: vertical jump r = 0.80, p = 0.02, countermovement jump r = 0.48, p = 0.02; females: vertical jump r = 0.30, p = 0.04, countermovement jump r = 0.80, p = 0.01), and crawl swim performance (males: r = -0.91, p = 0.001; females: r = -0.72, p = 0.04). BM had a 87% contribution to crawl swim performance in males and a 66% contribution in females. ULP and LLP showed < 50% contribution to crawl swim performance in both females and males. Conclusions BM was associated with crawl swim performance of adolescent athletes of both sexes. BM exhibited a stronger contribution to crawl swim performance than ULP and LLP in adolescent swimmers at the puberty window.